Self-learning support through access to related information on distributed VOD. (13th July 2010) - Iribe, Yurie; Yasuda, Takami; Yokoi, Shigeki
Self-learning using the internet can enable a user to acquire not only knowledge of the purpose of investigation, but also related information discovered in the investigation. However, existing Video On Demand (VOD) systems do not possess a function to effectively combine videos with texts, pictures and videos and provide them, nor can the related knowledge be acquired. Therefore, the purpose of this research is building a system that extracts information related to them and combines videos with them on distributed VOD. We clearly describe the relationships between video and related information through XML/RDF and sharing and combining of them.